Agroforestry Interactions in Rainfed Agriculture: Can Hedgerow Intercropping Systems Sustain Crop Yield on an Ultisol in Lampung (Indonesia)? - Suprayogo, Didik; Hairiah, Kurniatun; Van Noordwijk, Meine; Cadisch, Georg (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2010)
The productivity of rainfed agriculture land developed on Ultisols is limited by physical and chemical constraints. These problems can be solved and consistently high yields obtained only by the development of comprehensive manage-ment systems. In the 1980s, hedgerow inter-cropping was promoted initially for improving soil fertility and sustainability of crop production on nutrient-depleted soils. However the previous enthusiasm for hedgerow intercropping is unsupported by scientific evidence and its labour demand too high. The question remains, is there a window of opportunity where the biophysical principle of hedgerow intercropping is sound? Research to compare the long-term performance of crops and trees in hedgerow intercropping and monocluture cropping is needed. This research has been conducted at long-term field experiment station at the BMSF-Project, Lampung, Indone-sia. The experiment site had non-nitrogen-fixing peltophorum (PP), nitrogen-fixing gliricidia (GG) and alternate peltophorum and gliricidia (PG) hedgerow intercropping and maize / groundnut monoculture (C) treatments. We concluded that the net interactions related to soil fertility and competition for growth resources in peltophroum were positive for crop yield in PP and PG but negative for GG. Even so, the PP and PG sys-tems resulted in similar yields as monocropping; however, hedgerow intercropping considerably improved soil fertility attributes. Keywords: Agroforestry, crop yield, ultisols, tropics, sustainable